2023
DOI: 10.1038/s41598-023-45407-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mandibular condyles trabecular structure in patients with severe class III pattern: a computed tomography (CT) fractal analysis study

Saeed Afzoon,
Farhad Ghorbani,
Mahvash Hasani

Abstract: Class III malocclusion is a combination of dental and skeletal disorders that causes discrepancies in occlusion. Malocclusion can affect the structure of the Temporomandibular joint (TMJ) resulting in many problems, one of which is affecting the internal structure of the bone. This study aimed to examine the morphological features of class III patients’ trabecular structure of the mandibular condyle in comparison with normal class I individuals using fractal analysis (FA). To study the internal structure of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The literature in orthodontics shows that FD analysis has been performed in many studies to explore the impact of functional appliance treatment and malocclusion on mandibular condyles and to evaluate the effect of orthodontic treatment on the mandibular bone (15,28,(35)(36)(37)(38). In addition, Ok and Kaya, in their study investigating the connection between dental effects of RME (rapid maxillary expansion) treatment and the patency of the midpalatal suture suggested that fractal analysis can also applied to determine the modifications of midpalatal suture and alveolar bone following RME treatment (15).…”
Section: Resultsmentioning
confidence: 99%
“…The literature in orthodontics shows that FD analysis has been performed in many studies to explore the impact of functional appliance treatment and malocclusion on mandibular condyles and to evaluate the effect of orthodontic treatment on the mandibular bone (15,28,(35)(36)(37)(38). In addition, Ok and Kaya, in their study investigating the connection between dental effects of RME (rapid maxillary expansion) treatment and the patency of the midpalatal suture suggested that fractal analysis can also applied to determine the modifications of midpalatal suture and alveolar bone following RME treatment (15).…”
Section: Resultsmentioning
confidence: 99%
“…Since then, it has been a method used to assess changes in trabecular bone. Fractal dimension (FD), obtained from radiographs or tomographs [11], is a measure that allows interpretation of the microstructure of trabecular bone [12]. Higher FD values are associated with a complex bone structure, characterized by denser and less porous trabecular architecture [13].…”
Section: Introductionmentioning
confidence: 99%